Changing Spaces and Border Regimes: A Central Borneo Trajectory of Globalisation - Dave Lumenta (Jurnal Kajian Wilayah, 2010)
Outside the ideological connotations of globalisation, Southeast Asia has always been global throughout its history. Strategically situated on the major maritime trade routes linking ancient Europe, India and China, Southeast Asia has a long dynamic history marked by shifting power and the intense movement of people, commodities and cultural flows. The regions fluidity and cosmopolitanism is amply demonstrated by the abundance of cross-cultural influences, shared within the region, such as technology, religious syncretism, language, diaspora, and even food. The arrival of colonialism and the subsequent emergence of postcolonial nation-states in the region have significantly reconfigurated and reordered the patterns of human flows within the region. Border regimes have become prominent regulators for the movement of people and commodities across boundaries, such as the establishment of customs and immigration controls, designated for international routes and port of entries.On the other hand, numerous upland regions across mainland Southeast Asia, peripheral maritime regions such as the Sulu Sea, the Celebes Sea, and the internationally-partitioned island of Borneo, remain quasi-open and fluid spaces where people and commodities traverse international boundaries relatively unchecked by border controls. This indicates that states rarely reach that idealised omnipotence to exercise total and coherent power over space and societal mobility. This is especially true for postcolonial states around the world. State borders throughout Southeast Asia have generally been established in an arbitrary fashion, where ethnic, linguistic, social and economic borders never neatly intersected with formal state boundaries drawn on maps. As a result, shared ethnicity, language, identities and economic interconnectivity remain to transcend many state boundaries.